Authority and Incentives in Organizations - Matthias Kräkel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
The paper analyzes the choice of organizational structure as solution to the trade-off between controlling behavior based on authority rights and minimizing costs for implementing high efforts. The analysis includes the owner of a firm, a top manager and two division heads. If it is more expensive to incentivize the division heads, the owner will prefer full delegation of authority to them to replace their high incentive pay by incentives based on private benefits of control. In that situation, decentralization is optimal given that selfish behavior is more important than cooperation for maximizing returns, but concentrated delegation of full authority to a single division head is optimal for cooperation being crucial. If, however, incentivizing the division heads is clearly less expensive than creating incentives for the top manager, the owner will choose centralization given that cooperation is the dominating issue, but partial delegation if selfish behavior is crucial.
urn:nbn:de:bvb:19-epub-17237-7
Keywords: D21; D23; D86; L22; 330; authority; centralization; contracts; decentralization; moral hazard